Proserpine and Midas - Shelley, Mary Wollstonecraft, 1797-1851 (Salt Lake City, UT : Project Gutenberg, 2004)
"Proserpine and Midas" by Mary Wollstonecraft Shelley is a verse drama written in 1820 for children, with contributions from her husband Percy Bysshe Shelley. Based on Ovid's tale of Proserpine's abduction by Pluto, this blank verse drama reimagines the ancient myth from a feminist perspective, emphasizing the bond between mother Ceres and daughter Proserpine. When the young goddess vanishes, Ceres must confront death itself to recover her child. The play explores themes of separation, maternal love, and female solidarity through a community of women who face divine forces beyond their control. (This is an automatically generated summary.)
Wikipedia page about this book: https://en.wikipedia.org/wiki/Proserpine_(play)
Release date is 2004-09-01
S. Goodman and David Starner
Keywords: Mythology, Classical -- Drama; Proserpina (Roman deity) -- Drama; Midas (Legendary character) -- Drama